Computational morphogenesis – Embryogenesis, cancer research and digital pathology. (July 2018) - Siregar, Pridi; Julen, Nathalie; Hufnagl, Peter; Mutter, George L.
Abstract: Overall survival benefits of cancer therapies have, in general, fallen short of what was expected from them. By examining the many parallels that exist between embryogenesis and carcinogenesis, we discuss how clinical and fundamental cancer research can benefit from computational morphogenesis (CM) insofar as carcinogenesis is causally related to altered mechanisms underlying embryogenesis and post-embryonic tissue homeostasis. We also discuss about the critical role played by digital pathology (DP) since it constitutes the main source of data for the model-fitting and validation of CM-generated virtual tissues. Conversely, we outline how CM can provide support to DP by generating annotated synthetic 2D and 3D data that can be fed into machine-learning methods dedicated to the automated diagnosis of DP slides.